2019
DOI: 10.1177/1053815119883410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Read It Again! In Early Childhood Special Education Classrooms as Compared to Regular Shared Book Reading

Abstract: Read It Again! PreK (RIA) is a whole-class, teacher-implemented intervention that embeds explicit language and literacy instruction within the context of shared book reading and has prior evidence of supporting the language and literacy skills of preschool children. We conducted a conceptual replication to test its efficacy when implemented in early childhood special education classrooms relative to regular shared book reading. The randomized controlled trial involved 109 teachers and 726 children (341 with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Postintervention, children in the intervention condition (11 classes) scored significantly higher on vocabulary, morphosyntax, print awareness, letter knowledge, and phonological awareness measures than those in the control condition (eight classes). In contrast, Piasta et al (2020) did not find positive impacts of another shared reading intervention, Read It Again!, on language and literacy skills relative to a control condition in which teachers read the same books without the intervention lessons. This study was conducted with 726 children enrolled in 109 U.S. early childhood special education classrooms.…”
Section: Targeting Early Language To Improve Comprehensionmentioning
confidence: 75%
“…Postintervention, children in the intervention condition (11 classes) scored significantly higher on vocabulary, morphosyntax, print awareness, letter knowledge, and phonological awareness measures than those in the control condition (eight classes). In contrast, Piasta et al (2020) did not find positive impacts of another shared reading intervention, Read It Again!, on language and literacy skills relative to a control condition in which teachers read the same books without the intervention lessons. This study was conducted with 726 children enrolled in 109 U.S. early childhood special education classrooms.…”
Section: Targeting Early Language To Improve Comprehensionmentioning
confidence: 75%
“…As part of the larger study, up to 10 children per ECSE classroom were selected to participate; specifically, up to six children with disabilities and up to four typically developing peers who met the inclusion/exclusion criteria were eligible to participate (more information on enrollment procedures can be found in Piasta et al, 2019). Because teachers were completing numerous measures for the larger study, it was not deemed feasible for teachers to complete the SSTSES and PLBS on every child participating in the larger study.…”
Section: Methodsmentioning
confidence: 99%
“…Piasta, Justice, McGinty, and Kaderavek (2012) similarly demonstrated that preschool teachers benefit from support with conversational strategies but required more intensive support to the development of language developing strategies. Piasta et al (2020) in a randomised controlled trial study with 109 teachers and 726 children (children with disabilities and their peers) using the RIA shared book reading intervention found that there was a significant increase in teachers' provision of explicit instruction in print knowledge, vocabulary, phonological awareness and narrative.…”
Section: Implications Building Collaborative Partnershipsmentioning
confidence: 99%